The Performance of Cattle Trade in Indonesia: A Case Study at Ambarketawang Livestock Market in Yogyakarta Province - Nurtini, Sudi; Muzayyanah, Mujtahidah Anggriani Ummul; Kusumastuti, Tri Anggraeni (2012)
The objective of this study is trying to take up a unique social phenomenon in a traditional people community which has hereditary market mechanism system. Smallholder livestock farming was tending to be side - l ine farming with saving motivation. The study designed on the basis of economic aspect, especially on the rural economic network. The study conducted by document study, interview with key person and the manager of the livestock market. The results of this study showed that the number of the beef cattle transaction was significantly influenced (p<0.01) by the number of livestock coming in the market and the condition of the business of the market (R 2 = 66.96%). Partially, the number of livestock which were c oming to the market influenced positively significant (p<0.01) to the number of transaction, as well as the condition of the market. It was descriptively obvious that after stopping of beef cattle import in the middle of 2011, the transaction of cattle was dominated by cows and tends to increase. Transaction in the market reflected the number of beef cattle which would be slaughtered. Further, this condition should be concerning by the policy maker unless there would be running out of beef cattle population . Key Words: Cattle, Cattle trade, Livestock market